Performances of halide scintillators for the dosimetry based on gamma-ray spectrometry for environmental monitoring systems - Wanook Ji; Eunjoong Lee; Young-Yong Ji (Nuclear Engineering and Technology)
High pressure ion chambers (HPIC) and NaI(Tl) scintillation detectors are widely used to monitor the ambient dose equivalent rate H∗(10) within and around the Korean nuclear facilities. However, HPIC cannot provide spectrometric information and NaI(Tl) detector is limited in identifying nuclides, such as 131I, 134Cs, and 137Cs, released from nuclear facilities owing to its insufficient energy resolution. This study employed four halide scintillators – LaBr3(Ce), CeBr3, and SrI2(Eu) – to measure the ambient dose equivalent rate and detect gamma nuclides from measured energy spectrum. First, the pulse–shaping time in the signal processing unit was optimized for each scintillator. Second, energy resolution and counting efficiency were estimated for 137Cs and 60Co. Finally, an irradiation test was performed to estimate the dose rate. Based on these results, LaBr3(Ce) and NaI(Tl) were selected as in situ gamma spectrometry system for measuring environmental radiation, and field experiments were conducted near the Fukushima Daiichi nuclear power plant to measure the dose rate.